Kedudukan Hukum Anak Astra pada Hukum Waris Adat Bali Setelah Orang Tua Biologisnya Kawin Sah - I Putu Agus Suarnegara; I Nyoman Gede Sugiartha; Anak Agung Sagung Laksmi Dewi (Fakultas Hukum Universitas Warmadewa, 2022)
The position of legitimate children and Astra children (children out of wedlock) have different inheritance rights and relationships with the biological father's family. Legal children in general are the status of children born to parents who are legally married. While illegitimate children are children born outside of marriage. Astra's children (children out of wedlock) in the Marriage Law Article 43 paragraph (1) U explains that children born out of wedlock only have a civil relationship with their mother or their mother's family. Thus, an illegitimate child only has a relationship with his mother and his mother's family as well as in terms of inheritance, which means the child has no legal relationship with his father, as well as in terms of inheritance. However, if the parents carry out legal acts of acknowledging and ratifying the child, the child out of wedlock who is recognized has the same position as the legal child. Legitimate children can also replace the position of heirs and can inherit from both parents.